Using Actional Functional Model (AFM) To Improve Student's Speaking Skills - Meri Yosefa (Persatuan Guru Republik Indonesia Provinsi sulawesi Tenggara, 2021)
Based on initial observations in class X majoring in Mechanical, it appears that student's English speaking skills have not reached the expected level of mastery of learning. This condition is caused by the teaching strategy used by the teacher. The purpose of this study is to explain whether the Actional Functional Model (AFM) can improve the English speaking skills of class X students majoring in mechanical engineering at SMK Negeri 1 Batam. This research is a Classroom Action Research with two cycles carried out in class X of the Mechanical Engineering Department of SMK Negeri 1 Batam. At the end of each cycle, a speaking skill test was conducted. Quantitative data were collected through speaking skills tests, and qualitative data were taken from observations made by an observer. Then the data were analyzed based on quantitative and qualitative techniques. Based on the results of data analysis, it was found that (1) Actional Functional Model (AFM) can improve students' learning activities in speaking English, (2) AFM method can improve students' English speaking skills. Based on these findings, the Actional Functional Model (AFM) is recommended to be applied in teaching English. For further researchers, it is recommended to use similar research in other situations to see the effect of the Actional Functional Model (AFM) method and student learning outcomes.